Health economics : an international perspective - McPake, Barbara; Normand, Charles E. M.; Smith, Samantha, 1975-; Nolan, Anne (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Health Economics: An International Perspective is the only textbook to provide a truly international, comparative treatment of health economics. Offering an analysis of health systems across borders, the fourth edition of this key text has been updated and revised to take account of changes in a host of countries. This edition features an expanded introduction, providing better grounding for many of the examples that come in subsequent chapters and making it easier for non-health care experts to see the links between the theory, the examples, and the health care system components. It also boasts a re-structured format, dividing the book into two broad sections: the first focuses on ideas and principles, along with evidence on their applications in the health sector, while the second focuses on introducing core tools and techniques used in applied health economics research. Further updates to this edition include: two new chapters on applied econometrics; more discussion of how the need for healthcare and access to healthcare are defined and measured; a new chapter on emerging issues for health systems that are emanating from a series of global transitions both within (e.g., demographic change, epidemiological change, global resolution on universal health coverage) and without the health sector (e.g., economic transitions). Throughout the text, examples and illustrations are taken from a wide range of settings and world regions, providing a unique overview of the performance of different health systems"--
OCLC-licensed vendor bibliographic record.
Keywords: Medical economics; Medical economics -- Cross-cultural studies; BUSINESS & ECONOMICS / Finance; BUSINESS & ECONOMICS / Public Finance; BUSINESS & ECONOMICS / Economics / General